Note from the Editor-in-Chief - Sivakumaran, Nikita (Consilience, 2016)
Dear readers, It is my great pleasure to announce the official publication of Issue XV ofConsilience: The Journal of Sustainable Development. 2015 has been a pivotal year in sustainable development, with the global adoption of 17 Sustainable Development Goals (SDGs) marking a new path for international discourse. Over the past few months, the team at Consilience has been working to curate the diverse selection of articles in this issue. We hope this new issue will further an interdisciplinary examination and understanding of key target areas within the SDGs. Issue XV features a variety of topics across different geographical regions that together seek to confront inefficiencies that arise from a changing world. Adewumi and Oguntuase examine best practices of wastewater management across the world in order to provide recommendations for the Nigerian system. Ndubueze-Ogaraku, Onoja, and Monsi analyse the effects of an oil spill on the productivities of local livelihoods such as shellfish collection. Continuing the discussion of oil, Sabah, Palliam, and Al Salem consider how oil price volatility has affected the lives of those who live in oil-rich countries. These two articles together offer differing implications of a shift to alternative energy sources and how it will affect standards of living across the world. While all articles are country-specific in nature, they carry significant policy implications that can be widely adopted. For instance, Lie focuses on the theoretical foundations of the asymmetrical relationship between donor and recipient institutions that decrease the effectiveness of development aid. Mubazi’s article complements Lie’s piece with an examination of the challenges to aid effectiveness in the African subcontinent. Tyler considers the natural disaster environment of the United States and provides examples of green infrastructure that can aid in hazard mitigation. Hollender offers a case-study of Bolivia’s political climate and the presidency of Evo Morales in order to guide efforts of building sustainable alternatives to capitalist development. The opinion pieces in this issue provide insight into current efforts to fight gender inequality and the illegal ivory trade in Africa. Boyd reviews Nike’s corporate responsibility program, The Girl Effect, and describes an inherently capitalist design that seeks to enter a thus far untapped market segment. Williams discusses the attitudes of various stakeholders towards ivory trade and the potential for a legal system that would empower local communities. Finally, the articles in this issue’s Field Notes deliver primary data for issues of pastoral livelihoods and the economic and environmental impacts of private conservation efforts. In particular, Abate reviews range management practices used in southern Ethopia and the effects of agricultural policies. Similarly, Oyinbo determines, through quantitative analysis, the effects of livelihood diversification in farm households to the reduction of poverty. With the current movement towards private eco-system conservation efforts around the world, Hounshell’s article provides a cost-benefit analysis of the economic impacts arising from such measures in a study of the SAI Sanctuary located in the Western Ghats of India. Our mission remains to promote dialogue and understanding of issues in sustainable development that affect not only individual communities, but the greater collective well-being of our planet. Our authors have worked diligently to provide innovative perspectives to perpetual challenges in sustainable development. We invite you to think critically about their arguments, further our understanding of their claims, and challenge their assumptions. Through interaction between practitioners, scholars, and researchers, we hope the ensuing dialogue will offer fruitful solutions to the most pressing challenges facing our planet. We encourage you to continue engaging with the journal through your readership, submissions, and contributions to our Briefings column. As always, we welcome constructive feedback and hope that our work inspires you to engage with the issues. If you have any questions, comments, or concerns, please do not hesitate to contact us at contact@consiliencejournal.org. We hope you enjoy Issue XV. Regards, Nikita Sivakumaran Editor-in-Chief